2019
DOI: 10.1038/s41467-019-11470-9
|View full text |Cite
|
Sign up to set email alerts
|

Physiologically relevant reconstitution of iron-sulfur cluster biosynthesis uncovers persulfide-processing functions of ferredoxin-2 and frataxin

Abstract: Iron-sulfur (Fe-S) clusters are essential protein cofactors whose biosynthetic defects lead to severe diseases among which is Friedreich’s ataxia caused by impaired expression of frataxin (FXN). Fe-S clusters are biosynthesized on the scaffold protein ISCU, with cysteine desulfurase NFS1 providing sulfur as persulfide and ferredoxin FDX2 supplying electrons, in a process stimulated by FXN but not clearly understood. Here, we report the breakdown of this process, made possible by removing a zinc ion in ISCU tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
221
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(240 citation statements)
references
References 58 publications
(135 reference statements)
17
221
2
Order By: Relevance
“…It is known that hysteresis has physiological importance to buffer radical changes in the concentration of metabolites in biological systems [ 53 ]. The interaction between AtNFS1 and AtISD11 would be crucial since in the absence of the latter it was observed that AtNFS1 shows very low cysteine desulfurase activity, as was recently reported in humans [ 27 , 39 ]. Moreover, AtFH directly stimulates the cysteine desulfurase activity.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…It is known that hysteresis has physiological importance to buffer radical changes in the concentration of metabolites in biological systems [ 53 ]. The interaction between AtNFS1 and AtISD11 would be crucial since in the absence of the latter it was observed that AtNFS1 shows very low cysteine desulfurase activity, as was recently reported in humans [ 27 , 39 ]. Moreover, AtFH directly stimulates the cysteine desulfurase activity.…”
Section: Discussionmentioning
confidence: 73%
“…Frataxin is a protein that has been widely conserved through evolution in bacteria, yeasts, mammals, and plants without major structural changes [ 19 , 20 ]. Several functions were proposed in which frataxin would be involved, including iron homeostasis and respiration [ 21 ], heme metabolism [ 22 ], assembly of Fe-S centers [ 23 , 24 ], oxidative phosphorylation and oxidative stress [ 25 ], storage of Fe in mitochondria in a water-soluble and non-toxic form [ 21 , 26 ], and recently, its involvement in persulfide transfer [ 27 ]. Previously, we described the presence of frataxin from Arabidopsis [ 24 , 28 ] and maize [ 29 , 30 ] and the results indicate that it is an essential protein in plants, required for optimal activity of Fe-S proteins and it is also involved in protection against oxidative damage [ 24 , 28 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…The role of these metals in the FRDA pathology is completely unknown and therefore, the impact of a therapy focused on controlling cellular levels of these metals has not been addressed with the exception of a work using the fruit fly [225]. Among these metals, zinc might be of special relevance due to its ability to impair ISC assembly [15].…”
Section: Future Directions and Prospectsmentioning
confidence: 99%
“…Although the function of frataxin remains unclear, early studies observed a deficient activity of the iron-sulphur clusters (ISC) containing enzymes of the mitochondrial respiratory chain and Krebs cycle in heart homogenates, mitochondria from skeletal muscles, fibroblasts and lymphoblasts derived from patients [11,12]. In this line, several reports have detailed the function of frataxin as stimulator of ISC biogenesis by facilitating the persulfide transfer [13][14][15]. ISC are prosthetic cofactors, responsible for the activity of different enzymes which are involved in energy metabolism, iron metabolism, purine synthesis and DNA repair.…”
Section: Introductionmentioning
confidence: 99%
“…The prokaryotic cysteine desulfurase is a modestly active enzyme; whereas, the eukaryotic complex is a low activity system that requires FXN activation to meet cellular Fe-S cluster biosynthetic demands (5,18,(35)(36)(37). There is strong evidence that FXN has a role in stimulating the cysteine desulfurase and sulfur transfer chemistry for Fe-S cluster assembly (18)(19)(20)(23)(24)(25)(26)38).…”
Section: Substitutions Have Varied Effects On the Dimeric Binding Conmentioning
confidence: 99%